2008
DOI: 10.1210/jc.2007-1229
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Dehydroepiandrosterone Levels Are Correlated with Brain Dehydroepiandrosterone Levels, Elevated in Alzheimer’s Disease, and Related to Neuropathological Disease Stage

Abstract: These findings indicate that CSF DHEA and pregnenolone levels are correlated with temporal cortex brain levels of these neurosteroids and that CSF DHEA is elevated in AD and related to neuropathological disease stage. Neurosteroids may thus be relevant to the pathophysiology of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…In contrast to the majority of studies, Naylor and colleagues [125] reported that cerebral spinal fluid levels of DHEA are significantly elevated in AD, as are tissue levels in the temporal cortex, with the extent of elevation being correlated with disease severity, as assessed by the burden of β-amyloid plaques. Similarly, Brown and colleagues [126] reported increased DHEA concentrations in the brains and cerebral spinal fluid of patients with AD when compared with controls, even though mean serum concentrations of DHEA did not differ.…”
Section: Dhea and Admentioning
confidence: 79%
“…In contrast to the majority of studies, Naylor and colleagues [125] reported that cerebral spinal fluid levels of DHEA are significantly elevated in AD, as are tissue levels in the temporal cortex, with the extent of elevation being correlated with disease severity, as assessed by the burden of β-amyloid plaques. Similarly, Brown and colleagues [126] reported increased DHEA concentrations in the brains and cerebral spinal fluid of patients with AD when compared with controls, even though mean serum concentrations of DHEA did not differ.…”
Section: Dhea and Admentioning
confidence: 79%
“…ALLO and PROG protected the rat brain from post-injury edema and decreased production of pro-inflammatory cytokines (IL-1,TNF-α). In patients with Alzheimer's disease, the level of ALLO in the temporal cortex was significantly lower than in controls, in contrast to PREG and DHEA which concentrations were increased (Naylor, et al, 2008). Furthermore, ALLO enhanced myelination and reduced inflammatory processes in the animal model of NiemannPick type C disease (Melon, et al, 2008).…”
Section: Progesterone and Derivativesmentioning
confidence: 99%
“…Decreased levels of DHEA in aging people may increase vulnerability of the brain to such a damage. Age-related declines of neurosteroids have been postulated to play a role in the pathogenesis of neurodegenerative diseases (Naylor, et al 2008). Some results suggest that DHEAS may be a negative modulator of GABA A receptors.…”
Section: Dehydroepiandrosterone and Dehydroepiandrosterone Sulfate Estermentioning
confidence: 99%
“…It is enriched in the brain, and central nervous system (CNS) levels of this neurosteroid are considerably higher than serum and/or plasma levels in both humans and rodents (Marx et al 2006a(Marx et al , 2009Naylor et al 2010;Sripada et al 2013a, b;Weill-Engerer et al 2002). Pregnenolone levels in cerebrospinal fluid (CSF) (Caruso et al 2013;Naylor et al 2008) and serum (Caruso et al 2013;Marx et al 2006a) are correlated with pregnenolone levels in the CNS, suggesting that neurosteroid levels in more accessible tissues such as blood or CSF could serve as proxy or surrogate markers to elucidate pregnenolone regulation in brain.…”
Section: Introductionmentioning
confidence: 99%